Ubuntu-principled multi-layered AI-Guardrails Framework for promoting sustainable integrity practices in Higher Education Institutions - Micheal van Wyk (International Journal of Research and Applied Technology (INJURATECH), 2026)
This study employed a systematic literature review (SLR) to synthesize the existing literature and examine how an Ubuntu-informed, multilayered AI guardrails framework can be conceptualized to promote sustainable integrity in higher education. The SLR approach is suitable for mapping emerging evidence, clarifying key concepts, and identifying research gaps. The first step was to define eligibility criteria for the types of scholarly works to be included in the SLR, with a focus on the research questions. This approach was adopted to ensure transparency and replicability. Findings indicated that existing scholarship on AI guardrails, which focuses on the ethical, technical, and procedural dimensions of the responsible use of AI and sustainable integrity in higher education, is limited. Existing AI guardrail frameworks in higher education are misaligned with ethical, relational, and community-oriented principles of Ubuntu philosophy. Finally, the Ubuntu principles were integrated with current AI guardrail frameworks to strengthen sustainable integrity practices in teaching, learning, and institutional governance. The contribution of this framework moves beyond compliance-based guardrails towards ethically internalized practices, integrates African philosophy (Ubuntu) into AI governance, and balances technology, pedagogy, and humanity to support long-term sustainability, not just the detection of misconduct.